Early empiric anti-Mycobacterium tuberculosis therapy for sepsis in sub-Saharan Africa: a protocol of a randomised clinical trial. Issue 6 (6th June 2022) - Said, Bibie; Nuwagira, Edwin; Liyoyo, Alphonce; Arinaitwe, Rinah; Gitige, Catherine; Mushagara, Rhina; Buzaare, Peter; Chongolo, Anna; Jjunju, Samuel; Twesigye, Precious; Boulware, David R; Conaway, Mark; et al.
Abstract : Introduction: Sub-Saharan Africa shoulders the highest burden of global sepsis and associated mortality. In high HIV and tuberculosis (TB) prevalent settings such as sub-Saharan Africa, TB is the leading cause of sepsis. However, anti-TB therapy is often delayed and may not achieve adequate blood concentrations in patients with sepsis. Accordingly, this multisite randomised clinical trial aims to determine whether immediate and/or increased dose anti-TB therapy improves 28-day mortality for participants with HIV and sepsis in Tanzania or Uganda. Methods and analysis: This is a phase 3, multisite, open-label, randomised controlled clinical 2×2 factorial superiority trial of (1) immediate initiation of anti-TB therapy and (2) sepsis-specific dose anti-TB therapy in addition to standard of care antibacterials for adults with HIV and sepsis admitted to hospital in Tanzania or Uganda. The primary endpoint is 28-day mortality. A sample size of 436 participants will provide 80% power for testing each of the main effects of timing and dose on 28-day mortality with a two-sided significance level of 5%. The expected main effect for absolute risk reduction is 13% and the expected OR for risk reduction is 1.58. Ethics and dissemination: This clinical trial will determine the optimal content, dosing and timing of antimicrobial therapy for sepsis in high HIV and TB prevalent settings. The study is funded by the National Institutes of Health in the US. Institutional review board approval was conferred by the University of Virginia, the Tanzania National Institute for Medical Research, and the Uganda National Council for Science and Technology. Study results will be published in peer-reviewed journals and in the popular press of Tanzania and Uganda. We will also present our findings to the Community Advisory Boards that we convened during study preparation. Trial registration number: ClinicalTrials.gov (NCT04618198 ).